Multilayered, Package-Less SAW Sensors: Latest Developments - Pascal Nicolay; Hugo Chambon; Thomas Moldaschl (Proceedings, 2018)
Passive and wireless SAW sensors can operate in extreme environment. However, there is no mass-market application for this technology yet, due notably to the lack of an adequate sensor housing solution. Package-less SAW sensors are therefore promising. Here, guided waves that propagate in a protective multilayer structure are used, instead of SAWs. However, issues will arise from the use of a multilayer structure. In particular, thermo-mechanical effects will impact the behavior of the devices. A solution must also be found to embed the antenna in the stack. We present here the results of a numerical study of the thermo-mechanical effects, in two package-less structures. One possible antenna design is proposed and evaluated.